2018
DOI: 10.1186/s12936-018-2420-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro invasion inhibition assay using antibodies against Plasmodium knowlesi Duffy binding protein alpha and apical membrane antigen protein 1 in human erythrocyte-adapted P. knowlesi A1-H.1 strain

Abstract: BackgroundThe rapid process of malaria erythrocyte invasion involves ligand–receptor interactions. Inducing antibodies against specific ligands or receptors that abrogate the invasion process is a key challenge for blood stage vaccine development. However, few candidates were reported and remain to be validated for the discovery of new vaccine candidates in Plasmodium knowlesi.MethodsIn order to investigate the efficacy of pre-clinical vaccine candidates in P. knowlesi-infected human cases, this study describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 50 publications
4
32
1
Order By: Relevance
“…Recombinant protein expression was induced with 0.1 mM isopropyl-β-D-thiogalactopyranoside (IPTG; Sigma-Aldrich, St. Louis, MO). All recombinant proteins were solubilized, purified, and refolded as described elsewhere [47,54].…”
Section: Recombinant Protein Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant protein expression was induced with 0.1 mM isopropyl-β-D-thiogalactopyranoside (IPTG; Sigma-Aldrich, St. Louis, MO). All recombinant proteins were solubilized, purified, and refolded as described elsewhere [47,54].…”
Section: Recombinant Protein Expressionmentioning
confidence: 99%
“…Meanwhile, P. knowlesi recombinant proteins were expressed for this study using wheat germ cell-free system for immunoscreening using specific primers (S2 Table), the procedures were described elsewhere [47]. Recombinant PkDBPα protein expression was described elsewhere [47].…”
Section: Recombinant Protein Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture of P. knowlesi: Since the maintenance of P. knowlesi in-vitro in rhesus RBCs for several intraerythrocytic cycles was achieved in 1945, 27 attempts to develop a continuous in-vitro culture for this malaria parasite have never ended 28 . The long-term in-vitro culture system would allow full analysis of parasite-host cell interactions 29 , improve understanding of the biology of P. knowlesi such as the mechanism of invasion 30,31 and resistance markers 32 , and contribute to the development of new anti-malarial drugs and vaccines 31,33,34,35 . The study by Ball et al, (1945) indicated that target cells of P. knowlesi are not restricted to a certain age in macaques, however, in humans, it was found that P. knowlesi mainly invades reticulocytes 17,27 .…”
Section: Establishment Of the Continuous In-vitromentioning
confidence: 99%